Persistent Activation of Autophagy After Cisplatin Nephrotoxicity Promotes Renal Fibrosis and Chronic Kidney Disease - Fu, Ying; Xiang, Yu; Wu, Wenwen; Cai, Juan; Tang, Chengyuan; Dong, Zheng (Frontiers in Pharmacology, 2022)
Autophagy, a highly conserved catabolic pathway in eukaryotic cells, contributes to the maintenance of the homeostasis and function of the kidney. Upon acute kidney injury (AKI), autophagy is activated in renal tubular cells to act as an intrinsic protective mechanism. However, the role of autophagy in the development of chronic kidney pathologies including renal fibrosis after AKI remains unclear. In this study, we detected a persistent autophagy activation in mouse kidneys after nephrotoxicity of repeated low dose cisplatin (RLDC) treatment. 3-methyladenine (3-MA) and chloroquine (CQ), respective inhibitors of autophagy at the initiation and degradation stages, blocked autophagic flux and improved kidney repair in post-RLDC mice, as indicated by kidney weight, renal function, and less interstitial fibrosis. In vitro, RLDC induced a pro-fibrotic phenotype in renal tubular cells, including the production and secretion of pro-fibrotic cytokines. Notably, autophagy inhibitors blocked RLDC-induced secretion of pro-fibrotic cytokines in these cells. Together, the results indicate that persistent autophagy after AKI induces pro-fibrotic cytokines in renal tubular cells, promoting renal fibrosis and chronic kidney disease.